Military Veteran Status and Posttraumatic Stress Disorder Symptomatology Among Urban Firefighters: The Moderating Role of Emotion Regulation Difficulties. Issue 4 (April 2019) - Bartlett, Brooke A.; Gallagher, Matthew W.; Tran, Jana K.; Vujanovic, Anka A.
Abstract : Abstract: A significant portion of firefighters are military veterans, and both populations experience high rates of trauma and posttraumatic stress disorder (PTSD) symptomatology. We investigated main and interactive effects of military veteran status (MVS) and emotion regulation difficulties (ERD) with regard to PTSD symptom severity in firefighters. Covariates included trauma load, number of years in the fire department, and depressive symptom severity. The sample was composed of 839 (93.9% men; mean age = 38.4, SD = 8.5) trauma-exposed firefighters who completed a web-based questionnaire battery. Structural equation modeling was used. ERD were significantly, positively associated with PTSD symptom severity ( β = 0.30, confidence interval [CI] = 0.20–0.41, p < 0.001). A significant interactive effect was noted ( β = 0.07, CI = 0.01–0.14, p = 0.020); firefighters who endorsed MVS and greater ERD had the highest levels of PTSD symptom severity. It is vital that future work examine associations between MVS and relevant cognitive mechanisms for the purposes of informing effective screening, intervention, and prevention programs.